PENGARUH PELATIHAN KECERDASAN ADVERSITAS TERHADAP MOTIVASI BERPRESTASI PADA SISWA KELAS X DI SMA NEGERI 8 SURAKARTA - Nugraha, Redydian Adhitya; Karini, Suci Murti; Priyatama, Aditya Nanda (Jurnal Ilmiah Psikologi Candrajiwa, 2012)
EFFECT OF ADVERSITY INTELLIGENCE TRAINING ON ACHIEVEMENT MOTIVATION TO STUDENT IN CLASS X SMA NEGERI 8 SURAKARTA Redydian Adhitya Nugraha G0106081 ABSTRACT Each student has the same goal which is successful in his studies. In reaching for success there are barriers that must be traversed, among them is a lazy, not conducive learning ambience, not like a particular subject, and so on. Students are required to attempt to resolve the problems encountered with regard to the barriers. The efforts undertaken this is concrete students efforts to achieve success. Someone who is able to transform obstacles into success opportunities have a higher intelligence adversitas. Individuals who have the intelligence of a high adversity is the individual who is optimistic, think and act in a timely, unable to motivate themselves, dare to take risks, and future-oriented. This research aims to determine the influence of adversity intelligence training against an accomplished student motivation in class X in SMA Negeri 8 Surakarta. This research uses the technique of matching by comparing scores between the subjects group motivation accomplished control and experimental groups. Group experiment in this study were given preferential treatment in the form of training of intelligence adversity during a meeting with twice the time 240 minutes. Training provided by the two facilitators and three cofacilitator with method presentation and video footage as well as training materials have been compiled by researchers in the module. Data retrieval is performed using the Achievement Motivation Scale with the value of the validity 0,391 to 0,844 and reliability value 0,952. Based on the hypothesis test by Independent Sample T Test obtained value t count bigger than t table (3.447> 2.035) and P values ââless than 0.05 (0.002 <0.05) and hypotheses test by Paired Sample T Test obtained value of t count bigger than t table (3.241> 2.120) and P values ââless than 0.05 (0.005 <0.05) so that adversity intelligence training has an influence in improving student achievement motivation in class X in SMA Negeri 8 Surakarta. Â  Â  Key words: Training adversity intelligence, achievement motivation